Evaluation of functional performance and locomotion of children with cerebral palsy - Lewandowska, Renata; Krajewski, Stanisław; Kucharczuk, Magda (Journal of Education, Health and Sport, 2018)
Purpose. Demonstration of the author's motor assessment questionnaire as a tool allowing detailed evaluation of movement dissociation disorders in children with cerebral palsy and damaged pyramidal system.Material and Methods. The study included 19 children with cerebral palsy aged 4 to 16 years. Mean age: 8 years old (SD = 3.53). The research was performed in the Neuron Rehabilitation Centre in Bydgoszcz. A motor assessment questionnaire was used to examine the possibility of changing position from the lowest, i.e. lying back, to the highest, i.e. standing and walking. Based on the Gross Motors Function Classification Scale (GMFCS), children were qualified to specific functional levels from I to V. The Functional Mobility Scale (FMS) scale was used to examine the capability of locomotion at three distances: 5m, 50m and 500m. Total examination - using the motor assessment questionnaire, the GMFCS scale and the FMS scale - was used to determine dysfunctions and current skills of the subjects and predict their functioning and locomotion.Results. The range of points scored by children according to the motor assessment table was 7 to 46 out of 48. Based on the GMFCS scale, the subjects were qualified to levels from I to V, and according to the FMS scale - to eight groups depending on the locomotion capabilities. The results obtained by the study group in individual scales were compared.Conclusions1. The general functional performance of a child expressed by GMFCS level is significantly affected by factors not related to motor activity itself. This is confirmed by the lack of a close relationship between the motor skills assessment and GMFCS level. 2. Scores obtained in the motor assessment test in most cases are adequate to the capability of independent upright mobilization. 3. Scores obtained in the motor assessment test always determine the capability of walking on three distances according to the FMS scale. 4. Independent walking with the use of orthopedic support is possible for children, who obtained at least 30 points out of 48 in the motor assessment test. 5. It has been shown that the author's motor assessment questionnaire is useful for the motor assessment of children with cerebral palsy.